2011
DOI: 10.1002/oa.1141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial deformation on cranial morphogenesis in the south central Andes

Abstract: One of the most interesting issues of the interface between biology and culture is the artificial deformation of the skull. This modification is produced during early morphogenesis through the use of devices that alter the normal growth and development, to obtain a culturally established model. This paper, using a large cranial sample from the South Central Andes (1586 individuals), describes and documents a detailed morphometric study of the changes affecting the vault, cranial base, face, orbits and nasal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
2
12
0
4
Order By: Relevance
“…The intervention changes the normal shape of the head and restricts the development of the cranium in anterior-posterior and/or lateral directions, but permits compensatory growth of the skull-thus the cranial capacity remains constant. 6 Considering that the custom of artificial cranial deformation was widespread in the Carpathian Basin and might be an indication of the social status of individuals in the 5th-7th centuries, we can assume with good reason that, in the vast majority of cases, this practice should not have caused any neurological disorder or any other serious health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention changes the normal shape of the head and restricts the development of the cranium in anterior-posterior and/or lateral directions, but permits compensatory growth of the skull-thus the cranial capacity remains constant. 6 Considering that the custom of artificial cranial deformation was widespread in the Carpathian Basin and might be an indication of the social status of individuals in the 5th-7th centuries, we can assume with good reason that, in the vast majority of cases, this practice should not have caused any neurological disorder or any other serious health problems.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the types of cranial deformation, the classification of Dembo and Imbelloni 7 (see also Cocilovo et al 6 ), which is one of the synthetic works referred to most frequently in physical anthropology, was applied. In this way, 4 main types of cranial deformities could be distinguished, which are as follows.…”
mentioning
confidence: 99%
“…doi:10.17139/raab.2018.0020.02.04 La deformación artificial de la bóveda del cráneo es un fenómeno de dispersión mundial y que, particularmente en América, se ha encontrado en frecuencias muy altas durante la prehistoria, transformándose en objeto de interés por parte de la antropología biológica desde sus orígenes (Dembo e Imbelloni, 1938;Imbelloni, 1933;Moreno, 1882). Esta práctica es entendida como la alteración deliberada de la forma de cráneo, mediante el uso de fuerzas mecánicas externas, que influyen en el normal crecimiento y desarrollo de los huesos craneales durante la infancia (Buikstra y Ubelaker, 1994;Dembo y Imbelloni, 1938;Ubelaker, 1984 Desde fines del siglo XIX el estudio de las modificaciones artificiales de la bóveda del crá-neo, ha sido abordado para desarrollar diferentes aspectos tales como, el reconocimiento de la influencia de este fenómeno en la variación fenotípica craneofacial Cocilovo, Varela y O'Brien, 2010;Del Papa y Perez, 2007;Dembo y Imbelloni, 1938;Imbelloni, 1924Imbelloni, -1925Perez, 2006), el estudio de los efectos de la deformación craneal de la bóveda sobre el crecimiento y desarrollo craneofacial (Frieß y Baylac, 2003;Richtsmeier, Cheverud y Buikstra, 1984), como así también los estudios referidos a la clasificación de las deformaciones craneales (Broca, 1879;Dembo y Imbelloni, 1938;Imbelloni, 1924Imbelloni, -1925Virchow, 1892).…”
Section: Abstract Cranial Vault Deformations; Parana Delta; the Loweunclassified
“…If ACM increases cranial vault height, this would inflate stature estimates using the revised Fully method relative to predicted statures from regression-based methods, as the latter may not sufficiently account for outlying individuals who have modified crania. Previous studies have indicated that ACM can affect cranial vault and facial dimensions (Antón, 1989;Blackwood and Danby, 1955;Brown, 1981;Cheverud et al, 1992;Cocilovo et al, 2011;Kohn et al, 1993;Perez, 2007;Pomeroy et al, 2010;Rhode and Arriaza, 2006) so a preliminary evaluation of the effect of ACM on BBH was necessary.…”
Section: Effects Of Artificial Cranial Modification On Cranial Heightmentioning
confidence: 99%